Faith Ringgold - Turner, Robyn (Boston : Little, Brown, 1993)
Examines the life and work of the artist whose determination to be true to her African-American heritage brought about an influential new art form.
Booklist
School Library Journal
6.6
K-3
Keywords: Ringgold, Faith -- Juvenile literature; Afro-American artists -- Biography -- Juvenile literature; Artists -- United States -- Biography -- Juvenile literature; Ringgold, Faith; Afro-American artists; Artists; Art appreciation; Ringgold, Faith; African American artists -- Biography; American artists -- Biography; Women artists -- Biography; Art appreciation